The role of school leadership in promoting teachers' mental health and reducing their burnout (Comprehensive Journal of Science, 2026)
This theoretical study aimed to analyze the dialectical relationship between school leadership styles and teachers' mental health, focusing on the leader's role as a "psychological buffer" against burnout. The research employed a descriptive-analytical deductive method, reviewing modern psychological and educational literature and deconstructing theories of professional well-being, such as the PERMA model and Self-Determination Theory (SDT).The findings indicated that school leadership is the most influential independent variable in the institution's "psychological climate." Modern leadership styles (Transformational, Ethical, and Servant leadership) contribute significantly to reducing the three dimensions of burnout: emotional exhaustion, depersonalization, and reduced personal accomplishment. The analysis also revealed emerging challenges, such as "Digital Burnout," necessitating that leaders adopt procedural strategies like organizational justice and the "right to disconnect." The study recommended integrating mental well-being standards into school management quality assessments and training leaders in emotional intelligence to ensure sustainable educational output amidst ongoing crises.
Keywords: School Leadership, Mental Health, Teacher Burnout, Occupational Well-being, Libyan School.